1998
DOI: 10.1159/000045129
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Hematuria from an Arteriovenous Fistula Complicating an Open Renal Biopsy

Abstract: Arteriovenous fistulae and pseudoaneurysms are not rare after renal biopsy. The majority of these lesions (80%) are asymptomatic or show only transient symptoms. We present here a patient who developed life-threatening hematuria following an open renal biopsy. Arteriovenous fistula and pseudoaneurysm were detected in the biopsied kidney by color-coded Doppler sonography, confirmed by angiography, and the fistula was sealed by superselective arterial embolization with metallic coils. Color-coded Doppler sonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
1
21
1
1
Order By: Relevance
“…AVF and pseudoaneurysm can present with many different symptoms such as continuous abdominal bruit, palpable thrill, high output cardiac failure, thromboembolic phenomenon, reduced renal function and severe hypertension (6). As in previous studies (40,41), Omoloja et al reported that in their case report that the patient's creatinine level increased from a baseline of 0.8 mg/dL to 1.3 mg/dL 6 weeks after biopsy with an elevated blood pressure (10).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…AVF and pseudoaneurysm can present with many different symptoms such as continuous abdominal bruit, palpable thrill, high output cardiac failure, thromboembolic phenomenon, reduced renal function and severe hypertension (6). As in previous studies (40,41), Omoloja et al reported that in their case report that the patient's creatinine level increased from a baseline of 0.8 mg/dL to 1.3 mg/dL 6 weeks after biopsy with an elevated blood pressure (10).…”
Section: Resultsmentioning
confidence: 78%
“…However, an incidence of AVF that varies between 0.5 (4) and 16 % after renal biopsy (5) and complications developing up to 25 years later have been reported. The time period between the creation of the fi stula and the clinical presentation can be very variable (6), ranging from 7 to 365 days post-biopsy (6). Some of the complications such as AVF and pseudoaneurysm may be due to the needle size (7).…”
Section: Introductionmentioning
confidence: 99%
“…90% of the aneurysms are of fibrodysplastic origin [3]. Pseudoaneurysms and AV fistulae are a common finding (0.3–19%) after renal biopsy [4]. We believe that the pseudoaneurysm in our case was a rare complication of the embolectomy performed 12 months earlier.…”
Section: Discussionmentioning
confidence: 79%
“…Most pseudoaneurysms are asymptomatic [4], but if complications such as flank pain, gross hematuria, hypertension, arterial bruits, congestive heart failure or renal insufficiency occur, therapy is necessary. The treatment of a symptomatic aneurysm or fistula can be performed surgically or by interventional radiology.…”
Section: Discussionmentioning
confidence: 99%
“…4 Biyopsi sonrası AVF oluşumu ile klinik prezantasyon arasındaki süre biyopsi sonrası 7-365 gün gibi çok değişken olabilir. 5 Bizim olgumuzda ise biyopsi sonrası 3. gün transfüzyon gerektirecek kadar hematürinin devam etmesi üzerine renkli Doppler USG yapılarak AVF tanısı konmuştur. Mikroskobik hematüri ve perirenal hematom gibi minör komplikasyonlar genellikle biyopsi sonrası birkaç hafta içinde düzelirken, AVF'nin %70'inin ilk biriki yıl içinde spontan olarak gerilediği, %30'unun ise ilerleyip semptomatik olduğu bildirilmiştir.…”
Section: Discussionunclassified